Review of Complete Basic Immunization Services at Lok Bahu HealthCenter from January-July 2025 - Rahmania; Aprilia Nurlaila Zahro; Wa Ode Nurul Azkiah; Aniaya Salsabila; Hanis Kusumawati Rahayu; Zulhijrian Noor (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Complete basic immunization (CBI) is a public health priority program aimed at preventing Vaccine-Preventable Diseases (VPDs). Objective : This study reviews the implementation of CBI services at Lok Bahu Public Health Center, Samarinda City, during the period of January-July 2025. Research Methods/ Implementation Methods : This research employed a descriptive qualitative design involving health workers, posyandu cadres, health center management, pharmacy staff, and parents as informants. Data were collected through in-depth interviews, observations, documentation, and official document reviews, then analyzed through data reduction, data presentation, and conclusion verification using source, method, and data triangulation. Results : The results showed that the planning process was carried out through the Activity Proposal Plan (RUK) and cross-sectoral coordination; however, strategies to reach hard-to-access populations and non-vaccine funding support remained limited. The implementation stage faced challenges such as insufficient health personnel, delayed vaccine distribution, and community resistance toward immunization. The evaluation process through the Quarterly Mini Workshop functioned as a forum for identifying obstacles and follow-up actions across sectors, but inconsistencies between manual records and the ASIK application as well as delayed reporting from posyandu were still found. Conclusion/Lesson Learned : The achievement of CBI coverage in the Lok Bahu Health Center working area has not yet met the national target, influenced by planning, implementation, and evaluation factors that are not yet optimally integrated. Strengthening cross-sectoral coordination, financial support, stable vaccine distribution, adaptive risk communication, and synchronization of recording systems are required to sustainably improve immunization coverage.